Char Products From Bamboo Waste Pyrolysis and Acid Activation - Parthasarathy, Prakash; Mackey, Hamish R.; Mariyam, Sabah; Zuhara, Shifa; Al-Ansari, Tareq; McKay, Gordon (Frontiers in Materials, 2021)
Bamboo is found worldwide but is especially concentrated in tropical and subtropical areas with the major producing nations being China, Indonesia and Thailand with an annual production of 12 million tonnes. It has found uses in many applications such as: furniture, flooring, roofing, fencing, interior design and scaffolding in the construction industry. In this study, discarded waste bamboo furniture was used in the ground form as the raw material feedstock for the production of a series of biochars and activated carbons. The biochars were produced at different temperatures, namely, 723, 823, 923, 1023, 1123 and 1223 K, in a muffle furnace inerted with nitrogen and for different pyrolysis times. The product chars yields were 20 to 30% by weight of the raw material, surface areas were 100 to 350 m2/g. Other tests include elemental analysis, helium displacement density, pH, ICP-AES on a leachate sample. Four of the different temperature samples of biochar were used to adsorb the basic dye methylene blue and were shown to possess high adsorption capacities. Then, the same bamboo raw material powder was treated with acid and pyrolysed/activated in a nitrogen atmosphere at the same range of temperatures to produce activated carbons; these were characterised using similar test methods to the biochars. The yields are in the range 20 to 40% by weight of the raw material feedstock and the BET surface areas are in the range 200-600 m2/g. Three of the different temperature activated carbons were used to adsorb methylene blue and the results were compared with the biochar results. All the adsorption experimental isotherm results were analysed using conventional isotherm equations. The benefits and cost implications of both biochar and activated carbon routes are discussed. The methylene blue adsorption capacities are extremely attractive in the range 0.42-1.12 mmol/g (150-300 mg/g char product) and extend to over 2.35 mmol/g (700 mg/g) for the bamboo derived activated carbons. The micropore and mesopore volumes have been determined under the various char and activated carbon experimental conditions and coupled with the surface areas; these results have been used to explain the trends in the methylene blue adsorption capacities.